Pemanfaatan Bunga Telang (Clitoria ternatea L.) sebagai Teh yang bermanfaat bagi kesehatan masyarakat di Kampung Eduwisata Alam Sungai Masjid Kota Dumai - Ninik Nihayatul Wahibah; Delita Zul; Atria Martina; Yulminarti Yulminarti; Yuana Nurulita; Ennie Cahyadi; Ahmad Huesean; Muhammad Rizky Darmawan; Ikhlasul Febrianto; Tania Aisyah Rinaldi; Nurkhasanah Putri Rakhman (Unri Conference Series: Community Engagement, 2022)
Butterfly pea (Clitoria ternatea L.) known as ‘bunga telang’ is perennial plant originated from Indonesia. Butterfly pea flowers are edible flowers known to have active compounds such as antioxidants, anti-inflammatory, antibacterial, anti-cancer. These plants are grown at a lot of house-yard in Kampung Eduwisata Sungai Alam and are commonly used for natural dye for food and beverage. Therefore, objective of our programme was to introduce simple method for producing butterfly flower tea to Pokdarwis (Kelompok Sadar Wisata) Kampung Eduwisata Sungai Masjid. Result of the programme indicated that the participants were really enthusiastic involving in this training. Based on result of the questionnaire reveal that most of participants have positive perception to the training that contributing to improve their knowledge and skills in processing butterfly pea flowers. Percentage of participants who understand how to process the flower increase from 20% to 100% after the training. In addition, butterfly tea can be a commercially distributed that may improve economic level of the Sungai Masjid community. Furthermore, our programme motivates the community to take a part in conservation of natural resources.